Evaluation of irrigation and pruning on the phenology and yield of Theobroma cacao L. = Evaluación de riego y poda sobre la fenología y rendimiento en Theobroma cacao L. - Meneses Buitrago, Diego Hernán
Introduction. It is believed that only 0.5 % of the area planted worldwide with cocoa is irrigated. Water availability influences the rate of expansion of the tree canopy and thus light interception. Another extremely important factor is pruning, which influences the production of floral sprouts that will give rise to new fruits, influencing productivity. Objective. The objective of this study was to evaluate the effect of drip irrigation and pruning on the performance, phenology and phytosanitary behavior of cacao trees. Materials and methods. The study was developed between 2015 and 2016 in the Cauca department, Colombia. The six-year-old trees were subjected to two watering layers: L-100 % and L-0 % and two pruning levels: soft and strong. Total number of fruits, number of healthy and sick fruits, kg of wet and dry cocoa, fruit index and seed index, longitudinal and equatorial diameters and incidence of Moniliopthora roreri, Phytophthora palmivora and Monalonion dissimulatum were evaluated. The growth and development curves of the fruit throughout time were built. An experimental design of complete random blocks was used in an arrangement of divide plots. Results. Fruit index varied from 22 (T2) up to 33 fruits (T3), the seed index varied from 0.91 g (T4) to 1.14 g (T2). There were no other significant results for other variables. Conclusion. From a technical and economic point of view an optimal response to the interaction of irrigation with the two levels of pruning was observed because, with a timely application of watering and an adequate pruning management, crop performance can be increased, harvests can be programmed and better quality fruits can be obtained.